The efficacy and safety of combined chinese herbal medicine and western medicine therapy for COVID-19: a systematic review and meta-analysis - Lu Li; Hongliang Xie; Ling Wang; Aolin Zhang; Xuan Mou; Yifan Lin; Hongli Ma; Yu Wang; Jian Li; Jingshu Gao; Chi Chiu Wang; Ping Chung Leung; et al. (BMC, 2022)
Abstract Objective To systematically review the clinical efficacy and safety of Chinese herbal medicine (CHM) with and without Western medicine (WM) for different severity of COVID-19. Methods CNKI, PubMed, Wanfang Database, ClinicalTrails.gov, Embase, ChiCTR and ICTRP were searched from 01 Jan, 2020 to 30 Jun, 2021. Two authors independently assessed all the randomized clinical trials (RCTs) for trial inclusion, data extraction and quality assessment. Meta-analysis was conducted using Review Manager software (RevMan 5.4.1). Evidence was assessed using Grading of Recommendations Assessment, Development, and Evaluation (GRADE). Primary outcomes included total effectiveness rate. Secondary outcomes included improvements in symptom improvement and total adverse event rate. Different severity of COVID-19 patients was assessed in subgroup analysis. This study was registered with INPLASY, INPLASY202210072. Results 22 high quality RCTs involving 1789 participants were included. There were no trial used CHM alone nor compare placebo or no treatment. Compared with WM, combined CHM and WM (CHM-WM) treatment showed higher total effectiveness rate, lower symptom scores of fever, cough, fatigue, dry throat and pharyngalgia, shorter mean time to viral conversion, better Computerized Tomography (CT) image and blood results, fewer total adverse events and worse conditions (P < 0.05). Subgroup analysis showed that the total effectiveness rate of combined CHM-WM group was significantly higher than WM group, especially for mild and moderate patients. No significant differences in mortality and adverse events were found between combined CHM-WM and WM treatment. No serious adverse events and long-term outcomes were reported. Conclusion Current evidence supported the therapeutic effects and safety of combined CHM-WM treatment on COVID-19, especially for patients with mild and moderate symptoms. Long-term effects of therapy are worthy in further study.